A comparative study on phenolic profile, vitamin C content and antioxidant activity of Italian honeys of different botanical origin. (17th May 2013) - Perna, Annamaria; Intaglietta, Immacolata; Simonetti, Amalia; Gambacorta, Emilio
Summary The aim of our study was to identify and quantify the phenolic acids, flavonoids and vitamin C and to evaluate the antioxidant activity in ninety Italian honeys of different botanical origins (chestnut, sulla, eucalyptus, citrus and multifloral). The results showed that total phenolic and flavonoid contents varied from 11.08 to 14.26 mg GAE per 100 g honey and from 5.82 to 12.52 mg QE per 100 g honey, respectively. HPLC–UV analysis showed a similar but quantitatively different phenolic profile of the studied honeys. Vitamin C is present in all samples. Multifloral honey showed the highest amount of the detected total phenolic compounds and the highest vitamin C content. The DPPH value varied from 55.06 to 75.37%. Among the unifloral honeys, chestnut honey presented the highest levels of phenolic acids, flavonoids and vitamin C, which are closely associated with its high antioxidant activity. The results show that honey contains high amount of biologically active compounds, which play an important role in defining the nutraceutical quality of the product, and that the distribution of these compounds is influenced by the botanical origin.